Land Characteristics of Urbanised Areas and Cropping Pattern Changes in the Union Terhitory of Delhi - Sethi, M; Pandey, S (Annals of Arid Zone, 2016)
About 31% of the total 357 villages in the Union Territory of Delhi have become urbanized during 1951-1981. l’he lands in these villages were prime agricultural lands belonging to land capability classes II and III. Area earlier used for growing gram and barley is now being devoted to growing wheat. Horticultural crops are getting higher priority and large area is being devoted to vegetables and flowers commensurate with the increasing needs of the urban areas.